2021
DOI: 10.1186/s12929-021-00721-x
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in epigenetic cancer therapeutics: clinical advancement and emerging trends

Abstract: Epigenetic drug discovery field has evidenced significant advancement in the recent times. A plethora of small molecule inhibitors have progressed to clinical stage investigations and are being explored exhaustively to ascertain conclusive benefits in diverse malignancies. Literature precedents indicates that substantial amount of efforts were directed towards the use of epigenetic tools in monotherapy as well as in combination regimens at the clinical level, however, the preclinical/preliminary explorations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 352 publications
(482 reference statements)
0
68
0
Order By: Relevance
“…On the other hand, epigenetics acts at the genome scale by regulating multiple loci at the same time, and thus the targeting of individual epigenetic enzymes has an effect on a multitude of genes, reducing the likelihood of developing resistance. Reflecting this, epigenetic treatments are now part of the standard of care for several haematological malignancies; DNMT inhibitors are currently used for the treatment of AML and MDS, and HDACs are FDA-approved for the treatment of MM, CTCL, and peripheral T-cell lymphoma [374]. Additionally, at the time that this review was written, there were 83 registered clinical studies for epigenetic inhibitors in cancer (https://clinicaltrials.gov/; accessed on 6 July 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, epigenetics acts at the genome scale by regulating multiple loci at the same time, and thus the targeting of individual epigenetic enzymes has an effect on a multitude of genes, reducing the likelihood of developing resistance. Reflecting this, epigenetic treatments are now part of the standard of care for several haematological malignancies; DNMT inhibitors are currently used for the treatment of AML and MDS, and HDACs are FDA-approved for the treatment of MM, CTCL, and peripheral T-cell lymphoma [374]. Additionally, at the time that this review was written, there were 83 registered clinical studies for epigenetic inhibitors in cancer (https://clinicaltrials.gov/; accessed on 6 July 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These techniques can be applied to induce drug-resistance-cause protein degradation through the ubiquitin proteasome pathway by recruiting an E3 ligase to ligate the target protein for degradation. For instance, it has been reported that E3 ligase cereblon (CRBN) is highly expressed in lung cancer; thus, ligands for CRBN (lenidomide, thalidomide, pomalidomide) could be mounted in the PROTAC model to develop an anti-cancer therapy [ 147 ]. Likewise, the over-expression of Skp2 is observed in multiple cancers, as such the ligands for Skp2 in these cancers could be accommodated to target Skp2.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Since epigenetic machinery such as DNA methylation and histone modifications often work in parallel, the use of single agents in combination has recently drastically increased as this approach enhances their efficacy (102). Such a drug combination approach has also been exploited toward non-epigenetic targets (103). For example, combinations of HDAC-HSP90 inhibitors (104), HDAC-DNMT inhibitors (105), HDAC-KDM1 inhibitors (106), HDAC-BET protein inhibitors (107,108), HDAC-EZH2 inhibitors (109), and HDAC-PI3K inhibitors (110) showed good efficacy in different cancer cells.…”
Section: Dual and Other Inhibitorsmentioning
confidence: 99%